Trauma theory: trajectories of empirical investigations (Journal of Philosophy Culture and Political Science, 2024)
The article is devoted to a review of scientific publications representing the further development of the theory of trauma in Western cultural sociology. Its purpose is to analyze the modern historiography of trauma theory, its applicability in empirical research, which greatly expands its methodology. The collections that study the theory of trauma on the example of regions outside Europe and North America are considered; the application of trauma theory to the massive waves of repatriation associated with the collapse of colonial empires; and the use of trauma theory in post-colonial literary criticism. In connection with the scientific interests of the authors related to the formation of the Japanese national identity, special attention is paid to the works of A. Hashimoto. This line of research is seen as relevant for the purposes of forming a post-Soviet national identity in the light of identifying traumatic episodes of national history and comprehending the historical and cultural experience of the 20th century as a whole. The publication methodology is based on the analysis of historiography, which demonstrates the formation of the theory of trauma as an umbrella methodology, including studies of various humanitarian disciplines: sociology, cultural sociology, anthropology, postcolonial theory. The results of the presented article can be used in the light of studying the theory of trauma. This review is of practical use for the humanities of post-Soviet Kazakhstan, as a country that has experienced traumatic events and processes in its history, as an acquaintance with modern Western methodologies that study such traumas.Key words: trauma theory, national identity, decolonization.